Relationship Between Gonad Condition and Neurosecretory Cell Activity in the Green-Lipped Mussel, Perna canaliculus (Progressive Agriculture, 2014)
The relationship between the activity of neurosecretory cells and gonad development of Perna canaliculus was investigated. The variation in staining intensity of the neurosecretory cells in different ganglia was evaluated. Changes in staining intensity of neurosecretory cells (NSC) were correlated with gonad development. The variation in colour intensity (CI) resulted from differences in the amount of secretory materials within the NSCs. The neurosecretory cell types A and B showed a similar pattern of staining intensity, and showed correlation with gametogenesis and spawning. At the beginning of gonad development, these cells possessed very few granules and the number of granules in the cells increased with gonad maturation. The staining intensity decreased in A and B- cells just after spawning. Cell types C and D did not show any substantial changes in colour intensity with gonad changes.DOI: http://dx.doi.org/10.3329/pa.v18i2.18169 Progress. Agric. 18(2): 135 - 148, 2007